Pemodelan Arsitektur Enterprise Untuk Mendukung Sistem Informasi Manajemen Menggunakan Enterprise Architecture Di Stmik Bani Saleh - Amat Suroso (Sekolah Tinggi Teknik - PLN, 2016)
Achievement of the purpose of an enterprise face many challenges and changes that need a strategy for effective measures and efficient resource utilization. One strategy is important and increasingly used is the utilization and increased support for enterprise information systems. The implementation of this strategy on a mission elicits information system whose fulfillment requires an integrated way in the planning, implementation and control are aligned with enterprise business strategy. Development strategy for the fulfillment of the mission of information systems starting from planning to identify information needs and the possibility of using technology innovation to increase the performance of the enterprise. This planning can take advantage of Enterprise Architecture Planning methodology that produces data architecture, application architecture, technology architecture and implementation plan for the enterprise direction. Implementation plan in the form of a sequence of application development and migration / acquisition technology platform elaborated according to aspects of the business as a key driver, organizational aspects for the determination of the role of the resources of the perpetrators of implementation, the environmental aspects of information systems and information technology to bridge the state systems of today and that will be realized , as well as aspects of the application development mempertautkan the development stage with other development stages.